Clinical spectrum of SIX3-associated mutations in holoprosencephaly: correlation between genotype, phenotype and function. Issue 6 (2nd April 2009) - Lacbawan, F; Solomon, B D; Roessler, E; El-Jaick, K; Domené, S; Vélez, J I; Zhou, N; Hadley, D; Balog, J Z; Long, R; Fryer, A; Smith, W; et al.
Abstract : Background: Holoprosencephaly (HPE) is the most common structural malformation of the human forebrain. There are several important HPE mutational target genes, including the transcription factor SIX3, which encodes an early regulator of Shh, Wnt, Bmp and Nodal signalling expressed in the developing forebrain and eyes of all vertebrates. Objective: To characterise genetic and clinical findings in patients with SIX3 mutations. Methods: Patients with HPE and their family members were tested for mutations in HPE-associated genes and the genetic and clinical findings, including those for additional cases found in the literature, were analysed. The results were correlated with a mutation-specific functional assay in zebrafish. Results: In a cohort of patients (n = 800) with HPE, SIX3 mutations were found in 4.7% of probands and additional cases were found through testing of relatives. In total, 138 cases of HPE were identified, 59 of whom had not previously been clinically presented. Mutations in SIX3 result in more severe HPE than in other cases of non-chromosomal, non-syndromic HPE. An over-representation of severe HPE was found in patients whose mutations confer greater loss of function, as measured by the functional zebrafish assay. The gender ratio in this combined set of patients was 1.5:1 (F:M) and maternal inheritance was almost twice as common as paternal. About 14% of SIX3 mutations in probands occur de novo. There is a wide intrafamilial clinical range of features and classical penetrance is estimated to be at least 62%. Conclusions: Our data suggest that SIX3 mutations result in relatively severe HPE and that there is a genotype–phenotype correlation, as shown by functional studies using animal models.